Proyecto de inversión para la creación de un local dedicado al alquiler de vehículos de recreación en el balneario de Chachimbiro - Fernandez Guamanarca, José Luis (2025)
The present research work has the mission to demonstrate the integral viability in the creation of a local dedicated to the rent of quadrons and bicycles with the purpose of generating entertainment alternatives to the tourists that visit the spa of Chachimbiro. For this purpose, a theoretical study was carried out to demonstrate the validity of the topic proposed in this research. Likewise, as part of the field and methodological study, a certain sample study was carried out through surveys, which showed that the proposed proposal is accepted by the tourists who visit the Chachimbiro hot springs. Approximately 97% of those surveyed said they accepted the new recreational initiative to be carried out in Chachimbiro. From the financial point of view, the proposal is profitable because it has a positive NPV, equal to 535862, which means that the project is viable from the NPV point of view. The IRR is equal to 508 %, which indicates that the project is completely viable, since the IRR is much greater in value than the TMAR rate or any rate taken as a base reference. In this case the rate of 6% was taken, which is the maximum value that banks pay for interest in long term investments such as policies and related financial documents.